Research on Fabricating Luminescent Substance of Aluminum Tris-8 Hydroxide Quinoline (Alq3) for Offset Security Ink - Tran, Minh The; Vu, Quang Ninh; Tran, Van Thang (Old Journal, 2018)
Having important application to bring security factor for printing products, fluorescent colorless offset printing ink is more and more widely applied. Among the substances of content, fluorescent pigment determines the security property for this kind of ink. One of the most widely used fluorescent pigments is tris-8 hydroxy quinoline aluminum (Alq3). The characteristic of Alq3 is absorbing and emitting 510 to 520nm wavelength under 365nm UV light source. This article presents the results of research, fabrication and determination of Alq3 structure to ensure that the thermal stability, high fluorescence and particle size within 5µm. By controlling the technological factors (Na3CO3 selected as the alkalic medium at PH as 8 for the reaction, CH3OH selected as the dissolving solvent of qH,...) for the Alq3 synthesis reaction with modern analytical methods, the authors synthesized Alq3 with crystal particle size mainly around 5µm. the purity 95%-98% that is quite suitable as the pigment for security offset printing ink fabrication. Based on Alq3 synthesized, it is fabricated security offset printing ink from Alq3 amount 10% in weight with its viscosity as 24,430 Pa.s, fluorescent intensity the same as SICPA-Swiss ink but its wavelength as 514,432 nm quite different from the wavelength of SICPA-Swiss ink as 580,086nm.